Pengaruh Religius, Kualitas Layanan, Citra Destinasi Wisata, Dan Wisata Halal Terhadap Minat Wisatawan Muslim - Siti fatimah; Sugianto (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Tourism is growing rapidly in Indonesia, but halal tourism is diffic to compete with. Understanding the interest factors of Muslim tourists is important because global tourism offers opportunities. Tourist destinations now realize the importance of services according to Islamic principles. This research uses sample data of 90 respondents selected using the purposive sampling method. Data analysis was carried out using SPSS version 25, using statistical analysis such as classical assumption testing and hypothesis testing. The research results show that the religious variables, service quality and tourist destination image have a positive and significant influence on Muslim tourist interest, with a significance value of 0.000 each, which is smaller than 0.05. Meanwhile, the halal tourism variable has a positive but not significant influence on Muslim tourist interest with a significance value of 1.181, which is greater than 0.05. This shows that although halal tourism influences the interest of Muslim tourists, the effect is not significant compared to other variables. Keywords: Religious, Service Quality, Tourist Destination Image, Halal Tourism, Interest.